Analisis Penjualan Mobil Listrik Di Indonesia Dalam Rentang Waktu 2020-2023 - Ardiyanti, Dini; Kurniawan, Fedy; Raokter, Us; Wikansari, Rinandita (Journal of Economics and Management, 2023)
The automotive industry in Indonesia is growing rapidly with electric car sales increasing significantly by 2022. Hyundai is one of the largest electric car manufacturers in Indonesia, supported by the IK-CEPA (Indonesia-Korea Comprehensive Economic Partnership Agreement), a bilateral free trade agreement between Indonesia and South Korea in various fields such as trade in goods, services and other economic cooperation. The Indonesian government is also active in supporting the development of the electric vehicle industry through fiscal and non-fiscal incentives, as well as cooperation with Hyundai Motor Group in training electric vehicle technicians. Sales of electric cars in several brands and types such as Hyundai Kona EV, Hyundai Ioniq EV, and Lexus UX300e have increased from 2020 to October 2023, showing public interest in electric cars. Hyundai Ioniq 5 became the best-selling electric car in Indonesia in 2022, while the newly released Wuling Air EV in August 2022 also received attention for its affordable price and unique design. Indonesia has the largest nickel reserves in the world, so it has a great ability to make electric vehicle batteries. This will drive the development of the electric car industry in the country, with strong government support and increasing sales, the automotive industry, especially electric cars, will have a bright prospect to continue growing in the future.